SKALA PKBI Lampung sebagai wadah pengembangan remaja dalam bidang kesehatan seksual dan mental - Nurul Aini; Irhas Khasais; Rucy Hayungningrat Arum Puspita; Ana Mentari; Rima Yuni Saputri (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Sentra Kawula Muda Lampung (SKALA) is a youth development organization under the auspices of PKBI that focuses on educating adolescents about sexual and reproductive health. This study aims to describe the role of SKALA in increasing adolescents’ health awareness and to identify the challenges faced. Through interviews with the organization's leader and observation of activities, it was found that SKALA actively conducts outreach to schools and communities using creative methods. The positive impact includes an increased understanding among adolescents of the importance of maintaining reproductive health and promoting gender equality in leadership. A major challenge is the voluntary nature of the membership, limiting consistent participation. To address this, SKALA routinely organizes discussions and open recruitment to sustain organizational regeneration. Overall, SKALA plays a significant role in fostering a healthy and responsible young generation.